Diorganotin(IV) N-methyl-N-phenethyldithiocarbamate compounds induce cytotoxicity via apoptosis in K562 human erythroleukaemia cells - Sharifah Nadhira Syed Annuar,; Nurul Farahana Kamaludin,; Normah Awang,; Kok, Meng Chan; Norraphat Uttraphan Pim, (Penerbit Universiti Kebangsaan Malaysia, 2023)
Imatinib mesylate (IM), a leading treatment for chronic myeloid leukaemia (CML), has sparked worries about the possibility of CML patients developing a resistance to it. As a result, researchers are becoming more interested in organotin(IV) compounds due to their strong potential to be developed as anticancer agents and employed as an option to address the issues regarding IM-resistance therapy. Generally, this study is to determine the cytotoxicity induced by diorganotin(IV) dithiocarbamate compounds in K562 human erythroleukaemia cells. The two novel diorganotin(IV) compounds namely diphenyltin(IV) N-methyl-N-phenethyldithiocarbamate (C1) and dibutyltin(IV) N-methyl-N-phenethyldithiocarbamate (C2) were assessed their cytotoxicity via MTT [3-(4-5-dimethylthiazol-2-yl)- 2,5-diphenyltetrazolium bromide] assay and mode of cell death via Annexin V-FITC/PI assay with the duration treatment of 24 h. Both compounds displayed strong cytotoxicity in K562 cells. At concentration of 4.2 μM for C1 and 1.6 μM for C2, both compounds were able to induce 49.70% and 46.83% apoptotic events, respectively. The changes in cells’ morphological can also be seen 24 h after being exposed to the compounds at their respective IC50 doses. The findings demonstrated that the morphology of the cells was similar to apoptotic features, including cell shrinkage and the production of apoptotic bodies, meanwhile, the low levels of necrotic cells (<1%) also can be seen via cell lysis. In conclusion, both compounds possess the potential as antileukaemia drugs nevertheless, further studies on their action mechanism are required to ratify their qualities and suitability in the research of anticancer drugs development.